PELAJARAN SENI BUDAYA PADA PELAKSANAAN PPL MASA PANDEMI COVID-19 DI SMP 35 NEGERI PALEMBANG - Ilhaq, Muhsin; Fadhilah, Yenny (Besaung : Jurnal Seni Desain dan Budaya)
The implementation of Field Experience Practices (PPL) is a routine activity carried out every year by the Teacher Training and Education Faculty (FKIP), improving the quality of graduates and as a pre-condition for student teacher candidates for the school environment and gaining teaching experience. In contrast to the previous PPL implementation, the Covid-19 pandemic phenomenon occurred to coincide with the implementation of PPL in 2020. This unusual condition requires executors and other related parties to be wise in responding to this situation. The head of this research aims to find out information and describe the learning of cultural arts with the main subjects of fine arts, music and dance at SMP 35 Negeri Palembang by students participating in PPL during the Covid-19 pandemic, starting from the preparation of learning tools, learning implementation systems and techniques. evaluation. Qualitative is used to answer research questions, the policy of the principal who continues to carry out health protocols according to both central and local government regulations, student PPL participants continue to carry out learning using the application of their choice.